Anti-Oppressive Composition Pedagogies - Havard, Julia; Cardwell, Erica; Rao, Anandi (Radical Teacher, 2019)
The project of creating an anti-oppressive composition issue began with multi-disciplinary, multi-institutional collaboration between Julia Havard, Erica Cardwell, Anandi Rao, Juliet Kunkle and Rosalind Diaz, who crafted a call for community-building and community-transformation: to build tools, resources, and spaces for transforming our classrooms, specifically our writing classrooms; and to approach the teaching of composition in community, with accountability, and with urgency. This collaboration started as a working group at the University of California Berkeley, Radical Decolonial Queer Pedagogies of Composition, as a number of instructors at multiple levels of the academic heirarchy struggled with the differences between our writing classrooms and our research. Following Condon and Young (2016), Inoe (2015), and Gumbs (2012), our editing team wanted to create a context and process for rich unraveling of un-teaching oppressive systems through composition.